2000
DOI: 10.1016/s0169-4332(99)00362-1
|View full text |Cite
|
Sign up to set email alerts
|

Lead deposition onto fractured vitreous carbon: influence of electrochemical pretreated electrode

Abstract: Ž .Ž . We evaluated the electrochemical deposition of Pb II onto Fractured Vitreous Carbon FVC electrodes from solutions Ž . containing very low concentrations of lead in different electrolytes sulfate or chloride . To examine how the FVC surface state influences the lead deposition efficiency, the electrodes were subjected to different electrochemical pretreatments prior Ž . to the actual deposition process. The FVC electrode was used as a representative model of the vitreous carbon VC bulk, avoiding the poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Although, as well pointed out in one of the previously published papers, RMS[Rq] has not been established as a rigorous quantitative measure of the surface roughness and the surface quality, it has often been used for such purpose. Apparently, it is one of the simplest morphology parameters that can be used for the surface quality description. ,,− For HOPG-electrodes, we found that the average [RMS]Rq is 0.58 ± 0.07 nm, which is also sufficiently close to the previously reported value …”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Although, as well pointed out in one of the previously published papers, RMS[Rq] has not been established as a rigorous quantitative measure of the surface roughness and the surface quality, it has often been used for such purpose. Apparently, it is one of the simplest morphology parameters that can be used for the surface quality description. ,,− For HOPG-electrodes, we found that the average [RMS]Rq is 0.58 ± 0.07 nm, which is also sufficiently close to the previously reported value …”
Section: Resultssupporting
confidence: 89%
“…Contrary to the smooth and somehow homogeneous (in terms of morphology) surface of the HOPG-electrodes, the AFM image in Figure b revealed a large number of rather small features randomly distributed all over the FVC-electrode surface. The FVC surface was described more quantitatively in one of our previous papers . Therefore, we would like to mention that the nodular surface features are of rectangular or ellipsoidal shape with the following dimensions: 120−150 nm by 65 nm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis was based on a calculation of a standard deviation of all height values within the given (imaged) area, and expressed as the root-mean-square RMS[Rq] average of the surface roughness factor. For more details, see previous literature on roughness measurement by AFM. Results show that for the majority of films (C1, JU, TC, and Y3) RMS[Rq] is in the narrow range from 3.40 to 4.67 nm. In comparison with recent data by Lord and Buckley 26 the films are less rough as the asphaltene patches on mica reported to be about 8 nm.…”
Section: Resultsmentioning
confidence: 97%
“…This difference can be attributed to the fact that, in addition to mechanical polishing and ultrasonication, our GC surface was electrochemically treated as described in the Experimental Methods. Metal electrodeposition on such a modified GC surface , exhibits different behavior compared to that of typically prepared GC surface. …”
Section: Resultsmentioning
confidence: 99%